Blockade of HLA Antibody-Triggered Classical Complement Activation in Sera from Subjects Dosed with the Anti-C1s Monoclonal Antibody TNT009 - Results from a Randomized First-in-Human Phase 1 Trial - Mühlbacher, Jakob; Jilma, Bernd; Wahrmann, Markus; Bartko, Johann; Eskandary, Farsad; Schörgenhofer, Christian; Schwameis, Michael; Parry, Graham C; Gilbert, James C; Panicker, Sandip; Böhmig, Georg A (Transplantation, 2017)
Complement may play a key role in antibody-mediated rejection (ABMR). A promising therapeutic approach may be classical pathway (CP) inhibition at the level of early component C1. In this first-in-human, double-blind, randomized placebo-controlled phase 1 trial, we evaluated the safety and complement inhibitory effect of TNT009, a humanized monoclonal anti-C1s antibody. Sixty-four adult healthy volunteers received either single (n=48; 7 consecutive cohorts: 0.3-100 mg/kg) or 4 weekly infusions (n=16; 2 consecutive cohorts: 30 and 60 mg/kg per infusion) of TNT009 or placebo. To assess the effect of treatment on complement activity, sera from dosed subjects were analysed in a CP activation assay evaluating C3d deposition on HLA-coated microbeads spiked with alloantibodies. Single doses of TNT009 at 3-100 mg/kg uniformly and profoundly inhibited HLA antibody-mediated C3d deposition (≥86% after 60 min), whereby the duration of CP inhibition (2-14 days) was dose-dependent. Four weekly doses persistently blocked complement for 5-6 weeks. Ex vivo serum CP activity was profoundly inhibited when TNT009 concentrations exceeded 20 μg/mL. Infusions were well tolerated without serious or severe adverse events. Treatment with TNT009 was safe and potently inhibited CP activity. Future studies in patients are required to assess the potential of TNT009 for preventing or treating ABMR.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or used commercially without permission from the journal.